FEED ENRICHMENT WITH FISH OIL TO INCREASE EEL GROWTH RATE Anguilla bicolor (McCelland, 1844) - Mira Ismayanti; Tarsim Tarsim; Limin Santoso; Dwi Mulyasih (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2019)
Eel (Anguilla bicolor) is a export commodity fish in fisheries sector and has has high economic value but has slow growth. One method to accelerate eel growth is through feeding with the enrichment of fish oil. The aim of this research is to know the increase of growth rate of eel fish fed with the enrichment of essential fatty acids with fish oil. The study used 3 treatments and 3 replications ie A (0% fish oil / control), B (1.5% fish oil), and C (3% fish oil). Parameters observed included specific growth rate, feed consumption total, feed efiesiensi, fat retention, survival rate. The supporting parameters are water quality. The result of research obtained were tabulated and analyzed by excel 2013 program and SPSS v. 20.0. with 95% confidence interva and continued by Duncan test. The results showed that there was a significant effect (P <0.05) on the growth rate of eel fish fed with the enrichment of essential fatty acids with fish oil. Treatment C (3% fish oil) is the optimum dose because it has the best growth performance and best feed efficiency that is specific growth rate (4,61% ± 0,0075), total feed consumption (246,3 g ± 50,1), feed efiesiensi (42,5% ± 3,74), fat retention (2,97% ± 0,148) and survival rate (86,7% ± 11,5).